Women's voluntary work in the first and second Abbasid eras: (132-334 A.H. / 749-946 A.D.) - Abdel Hamid Taha, Maha Asaad (Al-Adab Journal, 2019)
This research aims to discuss the phenomenon of variety which means that it's essential for the person to donate from his own conviction without any obligatory conditions in order to perform the humanism, and this research discovers the calling, cultural, scientific, political, social and economic sides which had been established by the woman during the first and second Abassynian reign so that great authorities had appeared in accordance with this case and contributed with her brother (the man) in making the effective basic for stability, prosperity and establishment of the first Islamic Arab civilization.